Manajemen Sarana dan Prasarana dalam Meningkatkan Mutu Lembaga Pendidikan Islam - Harini, Hegar; Zukhrufin, Fina Kholij; Qoyimmah Wahyusi, Hana Dinul (JIE (Journal of Islamic Education), 2024)
This study discusses the management of infrastructure and facilities (sarpras) in improving the quality of Islamic educational institutions at the Qurrota A'yun Ponorogo Integrated Islamic Elementary School (SDIT) to describe the implementation of infrastructure management. Infrastructure management is an activity with stages of planning, procurement, inventory, care and maintenance, and disposal, which must be adjusted to the standards of the Minister of National Education Regulation Number 24 of 2007 at each level of education. The quality of infrastructure in an educational institution correlates with the quality of education. This research uses qualitative research by presenting data through observation, interview and documentation research stages. The data obtained will be checked for data validity using triangulation. These results and findings: (a) Quality development, if viewed from the infrastructure and infrastructure aspect, forms a team tasked with managing infrastructure, involving collaboration with all parties such as the principal, teachers, parents or guardians of pupils, students and the community. (b) The infrastructure management model is carried out at the planning stage through regular meetings, while the procurement stage is carried out using school operational funds and self-help from the community; the maintenance stage by providing motivation to students and making a joint agreement; the elimination stage by looking at the useful life of the goods. (c) Teachers manage infrastructure as planners, implementers, and users and guide students. (d) There are supporting factors for implementing infrastructure management through cooperation and budgets for infrastructure procurement. In contrast, the inhibiting factors need more awareness and consistency in Human Resources (HR) in the education environment.